2018
DOI: 10.1074/jbc.ra118.001975
|View full text |Cite
|
Sign up to set email alerts
|

Mini G protein probes for active G protein–coupled receptors (GPCRs) in live cells

Abstract: G protein–coupled receptors (GPCRs) are key signaling proteins that regulate nearly every aspect of cell function. Studies of GPCRs have benefited greatly from the development of molecular tools to monitor receptor activation and downstream signaling. Here, we show that mini G proteins are robust probes that can be used in a variety of assay formats to report GPCR activity in living cells. Mini G (mG) proteins are engineered GTPase domains of Gα subunits that were developed for structural studies of active-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
322
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(369 citation statements)
references
References 26 publications
7
322
1
1
Order By: Relevance
“…To increase Gs coupling, membrane of cells expressing Cys‐CRF1R mutants were treated with recombinant mini‐Gs; a truncated variant of Gαs . It has been shown that GPCRs bound to mini‐Gs proteins adopt similar active‐state conformations as those of Gs‐protein bound receptors . Indeed, yields of crosslinking on ClAc‐ligand/Cys‐CRF1R pairs increased by increasing the concentration of mini‐Gs in the probes (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…To increase Gs coupling, membrane of cells expressing Cys‐CRF1R mutants were treated with recombinant mini‐Gs; a truncated variant of Gαs . It has been shown that GPCRs bound to mini‐Gs proteins adopt similar active‐state conformations as those of Gs‐protein bound receptors . Indeed, yields of crosslinking on ClAc‐ligand/Cys‐CRF1R pairs increased by increasing the concentration of mini‐Gs in the probes (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…At the end of the incubation period, cells were lysed, and cAMP determined by HTRF (cAMP Dynamic 2 kit, Cisbio) using a Spectramax i3x plate reader (Molecular Devices). The plasmids for mini-G s , -G i and -G q , each tagged at the N-terminus with the LgBiT tag (Wan et al, 2018), were a kind gift from Prof Nevin Lambert, Medical College of Georgia.…”
Section: Cyclic Amp Assays By Htrfmentioning
confidence: 99%
“…Using this strategy, the study beautifully documents detection of GPCR activation at various subcellular locations including plasma membrane, the Golgi apparatus, and endosomes (8). More quantitative and kinetic information on GPCR activation can be obtained when mGs and GPCRs are tagged with BRET pairs, yielding robust and reproducible ratiometric measurements in multiwell assay format on plate readers (8). What if you do not have access to sophisticated instruments or feel uncomfortable doing live-cell microscopy or BRET measurements?…”
mentioning
confidence: 99%
“…In this issue of JBC, Nevin Lambert's group describes the development of a new arsenal of tools and assays to monitor GPCR activation directly and robustly using standard equipment available in most laboratories (8). The new technology is based on repurposing the so-called "mini G proteins" (mGs) originally developed as structural biology tools by Carpenter, Tate, and colleagues (9, 10), who co-authored this paper.…”
mentioning
confidence: 99%
See 1 more Smart Citation